BUSINESS STRATEGY, ACCOUNTING CONSERVATISM, TAX AGGRESSIVENESS - Yin Kuo, Chen (PEOPLE: International Journal of Social Sciences, 2024)
Different from literature studying the bi-variable relation between business strategy and accounting conservatism as well as tax aggressiveness, this research provides original ideas exploring the relation among business strategy and accounting conservatism through tax aggressiveness. Using the Taiwan data including high-technology and traditional industries, our results indicate that first, prospector companies are more tax aggressive, and are more accounting conservative than defender ones. Secondly, the positive effect of business strategy on accounting conservatism holds through increasing tax aggressiveness (reducing tax payment), implying prospector companies with more tax aggressiveness are more accounting conservatism than defender ones with less tax aggressiveness. Thirdly, the positive effect of strategy on conservatism through increasing tax aggressiveness in high-tech firms is stronger than that in traditional ones. This implies that compared to traditional firms, high-technology firms can more strengthen this positive effect through tax aggressiveness. Fourthly, this paper highlights the role of tax aggressiveness in driving association between business strategy and conservative accounting. Finally, our results are analogous to Higgins et al. (2015) and Hsieh et al. (2019)’s findings of U.S. sample companies, implying that some characteristics of Taiwan companies (e.g., access to capital market, tax deductibility of investment in R&D) appear to be similar to particularities of U.S. firms. This paper provides the evidence on a developing country (Taiwan) for investors and portfolio managers.